2019
DOI: 10.21203/rs.2.13599/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nurse-Patient Interaction and Self-Transcendence: Assets for a Meaningful Life in Nursing Home Residents?

Abstract: Background. Today, we face a shift to an older population worldwide and its consequences; a noteworthy part of older adults will need 24-hours nursing home care at the end of life. Finding new and alternative approaches to increase wellbeing among nursing home residents is highly warranted. Knowledge about nurse-patient-interaction, self-transcendence and meaning-in-life seems vital in order to guide clinical practice in how to best and efficiently boost wellbeing among older adults in nursing homes. Methods … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 88 publications
0
10
0
1
Order By: Relevance
“…Given the definition of loneliness, interventions can focus on two aspects: improving the quantity and quality of the support network and adapting expectations of interpersonal relationships to become more realistic ones (de Jong Gierveld et al, 2018; Lee et al, 2020). According to Haugan et al (2020, & 2021), the quality of the nurse–patient interaction can significantly improve older adults’ physical, emotional, social, functional, spiritual well‐being, joy‐of‐life and self‐transcendence in the LTC. In addition, Kamalpour et al (2021) proposed the use of an online community to provide the necessary social support, network and resources to engage older adults meaningfully and reduce their loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Given the definition of loneliness, interventions can focus on two aspects: improving the quantity and quality of the support network and adapting expectations of interpersonal relationships to become more realistic ones (de Jong Gierveld et al, 2018; Lee et al, 2020). According to Haugan et al (2020, & 2021), the quality of the nurse–patient interaction can significantly improve older adults’ physical, emotional, social, functional, spiritual well‐being, joy‐of‐life and self‐transcendence in the LTC. In addition, Kamalpour et al (2021) proposed the use of an online community to provide the necessary social support, network and resources to engage older adults meaningfully and reduce their loneliness.…”
Section: Discussionmentioning
confidence: 99%
“…Ageist stereotypes and discrimination encourage the marginalisation of older adults and contribute to their social exclusion (Haugan, Eide, et al., 2020; Haugan, Kuven, et al., 2020; Vitman et al., 2014). In this study, some participants had unconsciously internalised and manifested certain ageist stereotypes, which resulted in the older adults feeling like they were inferior to the young.…”
Section: Discussionmentioning
confidence: 99%
“…Such acceptance derives from meaningful dialogues about one's daily experiences as well as the experiences throughout one's life journey, namely opportunities to talk about ‘what is on one's mind’, which is termed the core of spiritual care (16). Therefore, nurse–patient interaction performs as a health‐promoting asset in NHs (13–15), supporting both ST, meaning‐in‐life and wellbeing in this specific context. Consequently, health professionals need knowledge about meaning‐in‐life, ST and nurse–patient interaction, and guidance in how to facilitate wellbeing by means of these approaches.…”
Section: Implications For Nursing Practicementioning
confidence: 99%
“…Research has shown that among religious/spiritual as well as non‐religions/non‐spiritual individuals, ‘being able to talk about what was on my mind’ was deemed most important. Being listened to, having one's faith/beliefs valued and being understood are all important aspects of health‐promoting nurse–patient interaction (13–15). Nevertheless, being able to talk about what was on one's mind has been reported the most important aspects of spiritual care (16).…”
Section: Introductionmentioning
confidence: 99%